Mean platelet volume is associated with periodontitis: a cross-sectional study - Chenying Zhou; Ye Liu; Jingjing Bai; Yi Luo; Jukun Song; Ping Feng (BMC Oral Health, 2024)
Abstract Background It is uncertain if mean platelet volume and periodontitis are related. The objective of this study was to examine the association between levels of mean platelet volume and moderate/severe periodontitis in adult persons who inhabit the U.S. Methods We screened 6,809 people from the National Health and Nutrition Examination Survey (NHANES 2009–2012). Mean platelet volume was measured in the Mobile Examination Centers (MECs) using the Beckman Coulter analyzer. The category of periodontitis was defined by the CDC/AAP using clinical periodontal parameters. Multiple logistic regression models were employed to examine the distribution for covariate differences across the various independent groups. Four models were employed to examine the relationship between mean platelet volume level and periodontitis. Smoothed curve fitting was utilized to confirm the linearity of the relationships. To determine the impact of factors on the connection between MPV and periodontitis, subgroup analysis and interaction testing were utilized. Results Results from the multiple logistic regression analysis indicate a significant association between moderate/severe periodontitis and the mean platelet level, even after considering any potential confounding variables (OR = 1.090, 95% CI: 1.019–1.166, P-value = 0.01211). Additionally, those in the upper tertile of mean platelet volume levels had a 21.6% higher probability of developing periodontitis when compared with those in the least tertile of mean platelet levels (OR = 1.216, 95% CI:1.052–1.406, P-value = 0.00816). Moreover, it showed a positive correlation between mean platelet volume (MPV) and moderate/severe periodontitis. Subgroup analyses indicated a positive association between the level of mean platelet volume and moderate/severe periodontitis among individuals who were under 60 years of age, had low income, were obese, never smoked, were heavy drinkers, had hypertension, and had no cardiovascular disease (p < 0.05). However, none of the subgroups exhibited significant interactions (p for interaction > 0.05). Conclusion A correlation has been found between mean platelet volume levels and periodontal disease in individuals residing in the United States.